2006
DOI: 10.1348/000709905x53138
|View full text |Cite
|
Sign up to set email alerts
|

Influences on cognitive engagement: Epistemological beliefs and need for closure

Abstract: There are individual differences in epistemological beliefs and motives that may influence the goals students pursue in learning settings and the nature of their cognitive engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
5
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 64 publications
(85 reference statements)
9
67
5
7
Order By: Relevance
“…However, by uncovering basic assumptions and blind spots, reflective questioning goes beyond assessing risk and uncertainty. Doubt and the questioning arising from it thus appear to be crucial for exploring one's general beliefs about knowledge and knowing (DeBacker & Crowson, 2006). We therefore adopt Locke et al's (2008) notion of doubt-the experience of not knowing-to depict this raw epistemological competence driving reflective questioning at the individual level (cf.…”
Section: Opening Up the Black Box Of Reflective Questioningmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by uncovering basic assumptions and blind spots, reflective questioning goes beyond assessing risk and uncertainty. Doubt and the questioning arising from it thus appear to be crucial for exploring one's general beliefs about knowledge and knowing (DeBacker & Crowson, 2006). We therefore adopt Locke et al's (2008) notion of doubt-the experience of not knowing-to depict this raw epistemological competence driving reflective questioning at the individual level (cf.…”
Section: Opening Up the Black Box Of Reflective Questioningmentioning
confidence: 99%
“…Human beings differ in their inclination to engage in reflection, particularly when they are facing unexpected events and puzzling experiences. DeBacker and Crowson (2006) found that a person's epistemological beliefs and motives determine the level of cognitive engagement (DeBacker & Crowson, 2006). People frequently engaging in non-rhetorical questioning thus appear to have a high need for cognition, a stable individual tendency to (not) engage in and enjoy effortful cognitive activity (Cacioppo et al, 1996).…”
Section: Opening Up the Black Box Of Reflective Questioningmentioning
confidence: 99%
“…Research indicates that students' epistemological beliefs influence cognition as well as motivation to learn (Bodin & Winberg, 2012;Bråten & Strömsö, 2006;DeBacker & Crowson, 2006; T. M. Winberg & Berg, 2007), which in turn are related to affective experiences during learning (Harackiewicz, Barron, Tauer, & Elliot, 2002;Pekrun, et al, 2006). Although there are different views on how epistemological beliefs should be construed, descriptions normally comprise a continuum from dualistic to relativistic beliefs.…”
Section: Influence Of Personal Variables On Emotionsmentioning
confidence: 99%
“…Bireysel epistemolojik inançlar basitten karmaşığa farklı şekillerde sıralanmaktadır (Ryan, 1984;Schommer, 1990;DeBacker ve Crowson, 2006). Kienhues, Bromme ve Stahl (2008), epistemolojik inançlarla ilgili tüm çalışmaların zaman içinde bu inançların basit olarak adlandırılan epistemolojik inançlardan karmaşık inançlara doğru değiştiğini belirtmiştir.…”
Section: Bilimsel Epistemolojik İnançlarunclassified